Spanish Adaptation of the Inventory Brief Child Abuse Potential and the Protective Factors Survey - Sahagún-Morales, Arturo; Ampudia Rueda, Amada; Chacón-Moscoso, Salvador; Sanduvete-Chaves, Susana; Carro Pérez, Ennio Héctor; Andrade Palos, Patricia (Frontiers in Psychology, 2021)
Child maltreatment is a public health problem with different consequences depending on the form of abuse. Measuring risk and protective factors has been a fertile ground for research, without involving instruments with sufficient evidence of validity. The aim of the study was to gather evidence of validity and reliability of the Inventory Brief Child Abuse Potential (IBCAP) and Protective Factors Survey (PFS) in the Mexican population. The instruments were translated into Spanish. In a non-probabilistic sample of 200 participants, the 7-factor model for the IBCAP [comparative fit index (CFI) = 0.984; root mean square error of approximation (RMSEA) = 0.067] and the 4-factor model for the PFS (CFI = 0.974; RMSEA = 0.061) were confirmed, showing adequate fit indices. Reliability was estimated and evidence of convergent, divergent, and discriminant validity was collected, controlling for effects of social desirability. We also report interpretability statistics of the scores. We achieved solid progress in the development of instrumentation that allows determining the presence or absence of protective and risk factors for child abuse.